Corporate Governance Dan Kinerja Keuangan: Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - amalina, nur; Roofi Kurniawati, Via; Adi Saputra, Wisnu (Jurnal Bingkai Ekonomi (JBE), 2024)
This research aims to measure the impact of corporate governance on financial performance in manufacturing companies in the consumer goods industry sector listed on the Indonesian Stock Exchange. The research methodology used is a collection of data from Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique in this research is purposive sampling technique with the amount of data used is 82. The independent variable in this research is the Principal of Corporate Governance. Meanwhile, the dependent variable is financial performance which is measured using Return on Assets. This research also uses control variables to help measure the relationship between Corporate Governance variables and Company Performance. The results of this research show that the board of directors and institutional ownership have a positive and insignificant effect on Return on Assets. Meanwhile, independent commissioners show a negative and significant influence on Return on Assets. For the control variable on company size (SIZE) the results show a positive and significant effect, and leverage shows the results show the results have a negative and significant effect on Return on Assets.